ON PEČARIĆ’S INEQUALITY IN INNER PRODUCT SPACES - Dragomir, Sever S. (Matematichki Bilten, 2003)
Some related results to Pečarić’s inequality in inner product spaces that generalises Bombieri’s inequality, are given.